Potential Utility of Ultrasound-Enhanced Delivery of Antibiotics, Anti-Inflammatory Agents, and Nutraceuticals: A Mini Review - J. Karim Ead; Arjun Sharma; Miranda Goransson; David G. Armstrong (MDPI AG, 2022)
Ultrasound technology has therapeutic properties that can be harnessed to enhance topical drug delivery in a process known as phonophoresis. The literature on this method of drug delivery is currently sparse and scattered. In this review, we explore in vivo and in vitro controlled trials as well as studies detailing the mechanism of action in phonophoresis to gain a clearer picture of the treatment modality and explore its utility in chronic wound management. Upon review, we believe that phonophoresis has the potential to aid in chronic wound management, particularly against complicated bacterial biofilms. This would offer a minimally invasive wound management option for patients in the community.